Users’ perception of the risk assessment screening in an emergency care service in Cape Verde - Spagnuolo, Regina Stella (2017)
Objective: To reveal users’ perception of the risk assessment screening in an emergency service. Methods: Qualitative case study of 17 users of the Adult Emergency Department (AED) of the Agostinho Neto Hospital located in Cape Verde, Africa. Open interviews were carried out from August to October 2012 and the data were analyzed using the thematic content analysis. Results: Three thematic categories emerged: 1) “Prior screening by nurses”; 2) “Emergency service: quick response to save lives”; 3) “Unawareness of the purpose of risk assessment”. Conclusion: Users have little knowledge of the risk assessment screening, which may contribute to overcrowding and affect the care of cases considered urgent.